Expression, purification and crystallization of the outer membrane lipoprotein GumB from Xanthomonas campestris - Jacobs, Melisa (2012)
GumB is a predicted outer membrane lipoprotein that is involved in the synthesis and/or secretion of xanthan gum. This exopolysaccharide, produced by Xanthomonas campestris, is valuable in industry because of its important rheological properties. Solution of the GumB structure will provide insight into the polymerization and/or secretion mechanisms of xanthan gum. GumB was overexpressed and purified and diffraction-quality crystals of native GumB were obtained. A complete data set was collected to 2.54 Å resolution with an R(p.i.m.) of 0.034. The crystals belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 84.4, b = 90.5, c = 120.7 Å.